The IMPACT OF THE PANDEMIC ON GLOBAL LOGISTICS PROCESSES - Nagy, Gábor; Bányai, Ágota; Illés, Béla (Advanced Logistic Systems - Theory and Practice, 2021)
The COVID-19 pandemic reminded society that, in addition to natural disasters, epidemics are also part of our past, present and future. Even if we cannot prevent the emergence of dangerous viruses, we must be prepared to mitigate their impact on society. It is clear that the COVID-19 epidemic, in addition to its severe physiological effects, has caused significant economic damage worldwide. Global supply chains in different industries face significant challenges. Not only is the economy affected by the virus; society as a whole is affected, leading to dramatic changes in the behaviour of businesses and consumers. The global supply chains that have shown a high level of stability and resilience in recent decades now face a number of disruptive factors. The pandemic adversely affected the entire chain in terms of both manufacturing and logistics processes, as well as a significant shift in demand. The pandemic highlighted the need to focus on three key areas to increase the resilience of supply chains: risk and flexibility, global transparency, and rapid response and decision-making. It can be concluded that the changes caused by the epidemic will make global supply chains shorter and more transparent through renewed strategies such as digitization, the tools of which are the building blocks of the DSN.